2017
DOI: 10.2147/ijn.s133787
|View full text |Cite
|
Sign up to set email alerts
|

Design of polyaspartic acid peptide-poly (ethylene glycol)-poly (ε-caprolactone) nanoparticles as a carrier of hydrophobic drugs targeting cancer metastasized to bone

Abstract: Treatment of cancer metastasized to bone is still a challenge due to hydrophobicity, instability, and lack of target specificity of anticancer drugs. Poly (ethylene glycol)-poly (ε-caprolactone) polymer (PEG-PCL) is an effective, biodegradable, and biocompatible hydrophobic drug carrier, but lacks bone specificity. Polyaspartic acid with eight peptide sequences, that is, (Asp) 8 , has a strong affinity to bone surface. The aim of this study was to synthesize (Asp) 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…Figure 2D confirmed the smooth surface and the absence of pores. These results are consistent with the literature in which NCs were also prepared from PCL and by the chosen method [32][33][34][35][36][37][38]. In addition, no presence of drug crystal was reported on particle surface.…”
Section: Field Emission Scanning Electron Microscopy (Fesem) and Transmission Electron Microscopy (Tem)supporting
confidence: 92%
“…Figure 2D confirmed the smooth surface and the absence of pores. These results are consistent with the literature in which NCs were also prepared from PCL and by the chosen method [32][33][34][35][36][37][38]. In addition, no presence of drug crystal was reported on particle surface.…”
Section: Field Emission Scanning Electron Microscopy (Fesem) and Transmission Electron Microscopy (Tem)supporting
confidence: 92%
“…Therefore BMP2/7 alone might even induce the osteoclast-mediated bone loss. Combined BMP2/7 and ATRA treatment by using local drug delivery approach such as BMP2/7 and ATRA loaded nanoparticles targeting bone niche might be better approach to treat both metastasized cancer and metastasis-caused osteolysis [ 40 ]. Similarly a combination of BMP2/7 and ATRA might be used for implant fixation in excessive bone resorbed implantation area via surface modified implants that can load BMP2/7 and ATRA, and release locally [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescent tagging of the liposomes showed that they accumulated mostly on the eroded bone surfaces. The optimum ASP repeating unit number was found to be from 4 to 10 for an effective bone–ASP interaction. …”
Section: Biomedical Applications Of Pasp and Its Derivativesmentioning
confidence: 99%